Optimal barn characteristics for high-yielding Holstein cows as derived by a new heat-stress model - E. Shoshani; A. Hetzroni (Animal, 2013)
Meticulous planning is required to minimize heat-stress conditions in barns. The objective of this study was to determine optimum barn characteristics for high-yielding dairy cows under Israeli (Mediterranean) summer ambient conditions, by using a new stress model that takes ambient temperature, relative humidity and wind velocity into account. During the summers of 2004 and 2005, three meteorological stations were alternately installed in 39 barns: two stations inside the barn at the prevailing downwind direction, and a third station outside the upwind end of the barn. Ambient temperature, relative humidity, wind speed and direction were measured and recorded every 10 min for 3 to 5 consecutive days at each barn in turn. The data were collected at different geographical and climatic conditions. Therefore, the data collected by an outside station were used as covariates. A heat-stress model was used to determine the threshold temperature (THRT) at which a cow begins to increase its respiratory rate; THRT was the response variable in the statistical model. The THRT model takes in account assumed values of a cow's physiological characteristics: daily milk yield of 45 kg, containing 3.5% fat, and 3 mm fur depth. The independent variables were: orientation, barn type, roof slope, roof ridge, marginal height, roof type (fixed or sliding) and barn width. Results showed that the optimal barn for high-yielding cows is the loose-housing type, oriented with its long axis perpendicular to the prevailing wind direction. Advantageous to the design would be an open ridge or pagoda with marginal height of over 4.7 m for north-south orientation and over 5 m for east-west orientation, roof slope over 11%, and barn width between 43 and 51 m for north-south orientation but lower than 42 m for east-west orientation. A sliding roof was also found to be an excellent solution when outside yards are banned by environmental regulations.